The journal of infectious diseases. - Infectious Diseases Society of America; HIV Medicine Association (Oxford : Oxford University Press, 1904)
Published continuously since 1904, The Journal of Infectious Diseases (JID) is the premier global journal for original research on infectious diseases. The editors welcome Major Articles and Brief Reports describing research results on microbiology, immunology, epidemiology, and related disciplines, on the pathogenesis, diagnosis, and treatment of infectious diseases; on the microbes that cause them; and on disorders of host immune responses. JID is an official publication of the Infectious Diseases Society of America.
"Published on behalf of Infectious Diseases Society of America and HIV Medicine Association"--Home page.
Description based on online resource; title from home page (viewed on October 3, 2016).
Keywords: Communicable diseases -- Periodicals; Diseases -- Causes and theories of causation -- Periodicals; Medicine -- Periodicals